APLICAÇÃO DO MÉTODO CANGURU EM NEONATOS COM BAIXO PESO - Bispo, Joicielly França; César, Talãine Larissa dos Santos; Oliveira, Lázaro Heleno Santos de; Santos, Clécia Almeida; Veiga, Larissa de Lima Pessoa (Gep News, 2019)
Trabalho apresentado durante o I MASMI